Pengaruh Digital Marketing, Brand Preference dan Product Quality Terhadap Buying Decision Product skincare Avoskin - Nur Hanifah; Ari Susanti (Airlangga Journal of Innovation Management, 2023)
This study aims to identify and analyze the influence of digital marketing, brand preference, and product quality on buying decision of Avoskin skincare products. Skincare has become an important topic in the beauty industry. Along with the development of digital technology, digital marketing has become a significant factor in influencing consumer purchasing decisions. The study employed a survey method with cosmetic customers who purchased Avoskin Skincare products. This study utilized a purposive sampling approach approximately 100 Avoskin Skincare's users. Hypothesis testing involved convergent validity, discriminant validity, composite reliability, AVE, cronbach alpha, and coefficient of determination tests. Based on the data analysis results, this study found that the digital marketing, brand preference, and product quality variables have a significant influence on the buying decision of Avoskin skincare products. This research has important implications for understanding the influence of digital marketing, brand preference, and product quality on the buying decision of Avoskin skincare products. In a research perspective, this study contributes to knowledge in the areas of digital marketing and consumer behavior. In a practical standpoint, these findings can be utilized by Avoskin management to optimize their digital marketing strategies, strengthen brand preference, and enhance product quality, thereby influencing consumer purchasing decisions and achieving success in the market.